EWC confidential: Confidentiality in European works councils and how representatives deal with it. Case study and survey insights - Lise Meylemans; Stan De Spiegelaere (European Trade Union Institute (ETUI), 2020)
The idea behind the establishment of European Works Councils (EWCs) is that these are bodies which should be informed and consulted on company decisions and actions. However, this flow of information is often disrupted by confidentiality constraints imposed by management. Three central research questions are: (1) what are the different practices of confidentiality and the withholding of information in EWCs; (2) what are the different handling strategies EWC representatives use in order to deal with confidential information; and (3) how do these handling strategies affect the functioning of the EWC and the employee representatives themselves? The survey findings generally confirm the observations based on the case studies: EWC members who think management withholds information are also more likely to feel limited in discussing information because of the 'confidential' labelling; at the same time, EWC members who think management shares all information also feel much more free to talk about that information.
Keywords: 330; Works Council; European labor law; Confidentiality; Survey; Belgium; Netherlands; Betriebsrat; Europäisches Arbeitsrecht; Geheimhaltung; Befragung; Belgien; Niederlande